SOCIOLOGY OF HEALTH AND ILLNESS - Lutfey, Karen (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this course, we begin with the idea that we cannot understand the topics of health and illness simply by looking at biological phenomena and medical knowledge, but, instead, we must also consider a variety of social, political, economic, and cultural forces. Sociologists of health and illness (also known as "medical sociologists") use sociological perspectives and methods to understand topics such as: social meanings of illness; patterns in the distribution of health and illness; how people seek help for and manage their illnesses; how doctors, nurses, and patients interact with each other; how various healthcare settings functions as institutions; and social movements surrounding health, including the ways some deviant behaviors are "medicalized" while others are not. Why is it that poorer people are more likely than wealthier people to have health problems and shorter life expectancies? Why is it the case that, when faced with very similar circumstances, some people seek medical attention while others do not? What happens when these people come in contact with the medical system? As a society, how do our labels for "medical problems" change over time so that medical jurisdiction over a problem can expand or recede?